Challenges Faced by Teachers in Implementing Digital Educational Games Developed Through Training Programs in Schools - Alfi Nura Fauzan; Rina Mawarni; Tia Rosanna Tambun; Zalfa Zahiroh; Elya Siska Anggraini (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The development of digital technology has created new opportunities in the field of education, including early childhood education. One form of technology integration in learning is the use of digital educational games, which can help teachers create a more engaging, interactive, and enjoyable learning experience for children. This study aims to examine the implementation of digital educational games developed through education and training programs and to identify the challenges teachers face in applying them in schools. This study employed a qualitative research method with teachers from a private kindergarten in Medan City as the research subjects. Data were collected through observation, interviews, and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that digital educational games have significant potential as an attractive learning medium for early childhood learners. However, several challenges remain in their implementation, including limited digital literacy among teachers, insufficient experience in integrating games with learning materials, and the time required to adapt to new technologies. Therefore, further training and continuous mentoring are needed to ensure that digital educational games can be utilized optimally in early childhood education (ECE) learning environments.